Rising food prices: What should be done? - Braun, Joachim von (International Food Policy Research Institute, 2008)
The sharp increase in food prices over the past couple of years has raised serious concerns about the food and nutrition situation of poor people in developing countries, about inflation, and-in some countries-about civil unrest. Real prices are still below their mid-1970s peak, but they have reached their highest point since that time. Both developing- and developed-country governments have roles to play in bringing prices under control and in helping poor people cope with higher food bills. In 2007 the food price index calculated by the Food and Agriculture Organization of the United Nations (FAO) rose by nearly 40 percent, compared with 9 percent the year before, and in the first months of 2008 prices again increased drastically. Nearly every agricultural commodity is part of this rising price trend. Since 2000-a year of low prices-the wheat price in the international market has more than tripled and maize prices have more than doubled. The price of rice jumped to unprecedented levels in March 2008. Dairy products, meat, poultry, palm oil, and cassava have also experienced price hikes. When adjusted for inflation and the dollar's decline (by reporting in euros, for example), food price increases are smaller but still dramatic, with often serious consequences for the purchasing power of the poor. National governments and international actors are taking various steps to try to minimize the effects of higher international prices for domestic prices and to mitigate impacts on particular groups. Some of these actions are likely to help stabilize and reduce food prices, whereas others may help certain groups at the expense of others or actually make food prices more volatile in the long run and seriously distort trade. What is needed is more effective and coherent action to help the most vulnerable populations cope with the drastic and immediate hikes in their food bills and to help farmers meet the rising demand for agricultural products.